Afrahat, Mowa XX: O trosce o biednych (Demonstratio XX: De sustentatione egenorum, PSyr 1, 893-930) - Uciecha, Andrzej (Vox Patrum, 2021)
The discourse On the Support of the Poor is the 20th in the collection of Aphrahat’s Demonstrationes. The Persian sage continues and develops his argument against Judaism and particularly rabbis of Babylonian diaspora. The proper understanding of this discourse demands the knowledge about the social and religious context of the Church in Persia in the 4th century AD. The text might point at difficult situations of Christians under persecutions launched by Shapur II, king of Persia. Unaware of crucial differences between Judaism and Christianity, some Christians visited synagogues and benefited from Jewish charitable institutions. As a teacher, the Persian sage constantly encourages his audience to undertake caritas christiana and back those Christians who already support the needy.